Firebreather [videorecording (DVD)] - Chung, Peter (Cartoon Network : Warner Bros., 2011)
Delivers fierce action in the clash of two worlds where dragons roam the Earth and past secrets are exposed. At the center of it all, teenager Duncan struggles to find his place as half-Kaiju and half-human.